In Situ Characterization Techniques Applied in Photocatalysis: A Review. Issue 3 (22nd December 2022) - Mu, Chunxia; Lv, Chongyang; Meng, Xiangchao; Sun, Jianhua; Tong, Zhangfa; Huang, Kelei
Abstract: Photocatalysis, as one of the hopeful technologies to overcome the issues of energy shortage and environmental pollution, has increasingly attracted attention. In situ characterization technology, which can observe the dynamic changes of catalysts in photocatalytic reaction in real time, plays a crucial part in the development of designing highly efficient photocatalysts and investigating their mechanism. This review introduces and summarizes primary applications of in situ characterization techniques in photocatalysis, including in situ investigation of the morphology and chemical structure of photocatalysts, photogenerated charges transfer, spatial distribution, and surface reaction pathways. Suggestions for future development of in situ characterization techniques in photocatalysis have prospected at the end. Abstract : In situ characterization techniques are conducted under actual‐ or near‐actual‐reaction conditions. These advanced characterizations provide opportunity to probe the dynamic change of morphology and structure, the charge transfer and distribution, and the detection of surface species and reaction intermediates.